Determinant Factors of The Performance Indicator of Local Government (Study towards Performance Indicator of Economic Growth and Open Unemployment Rate in Sidoarjo Regency) - Andy Kurniawan (Wacana Journal of Social and Humanity Studies, 2017)
Indicator of performance is an aspect to evaluate how successful local government is in carrying out development plan that had been established previously. The indicator is frequently referred to as Key Performance Indicator (Indikator Kerja Utama/IKU) stated in Medium-Term Development Planning of Local Government (Rencana Pembangunan Jangka Menengah Daerah/RPJMD), a document elaborating 5-year development planning. Implementation of development programs and activities by local government is an effort to achieve the targeted performance. Various, different factors affect successful achievement of the indicators of performance. The objective of the study was to describe several factors that affected the achievement of the development performance indicator, more particularly one for economic growth (Pertumbuhan Ekonomi/ PE) and open unemployment rate (Tingkat Pengangguran Terbuka/ TPT). The descriptive quantitative study analyzed quantitative indicators to describe specific dimension of the economic growth and open unemployment rate. Based on the analysis, the determinant factors for the economic growth in Sidoarjo were financial services and insurance sector, as well as unemployment variable, while those of the open unemployment rate were number of unemployment supported by inflation rate, economic growth and education level. In other words, local governments should focus on the most determinant factors to get priority for intervention programs and local government activities.